Studies of genetic variability, correlation and path coefficient for various characters in French Bean: Genetic variability in the French Bean (SAARC Journal of Agriculture, 2022)
The research was conducted during the Rabi season of 2019-2020 on 32 genotypes of French bean (Phaseolus vulgaris L.) to evaluate genetic variability, correlation coefficient and path coefficient. The genotypes were studied for 13 different characters of growth and yield attributing characters in Randomized Block Design with three replications for each genotype. All characters recorded higher PCV value over GCV thereby indicating the influence of environmental factors in their expression. High heritability observed in all the characters studied and high heritability coupled with high genetic advance found in the parameters viz. number of pods per plant, average pod weight, 100 seed weight and pod yield per plant. Correlation coefficient analysis showed pod yield had significant and positive correlation with number of pods per plant, pod length, average pod weight and 100 seed weight. Path analysis revealed that maximum positive direct effect w.r.t pod yield per plant was brought about by the parameters viz. 100 seed weight, days taken to marketable maturity, number of seeds per pod, number of pods per plant, average pod weight, pod width and pod length hence, should be given more importance for genetic improvement to bring about an increase in overall production of french bean through enhanced pod yield per plant.SAARC J. Agric., 20(2): 83-91 (2022)